The factors and effect of delay in government construction project (case study in Kuantan) - Mohd Rosazuwad, Mohamad@Muda (2010)
The problem of delays in government construction industry is a global phenomenon and there is no exception. The main purpose of this study is to identify the delay factors and the effect on the project completion. Earlier study either considered causes or the effects of project delays, separately. This study takes an integrated approach and attempts to analyze the impact of effects. A questionnaire survey was conducted to identify the causes and effects delay from contractors and clients. About 40 respondents participated in the survey. This study identified the most important causes of delay from a list 45 different causes and 5 different effects of delay and the recommendation to reduce the delay. The most important causes were delays in contractor's payments to subcontractors, shortage of material in construction, delays in sub-contractors, change in material, the weather condition, shortage of manpower (skilled, semi-skilled and unskilled labour), construction works involve huge amounts of money, unpunctually material delivery, labour productivity, and unavailability of incentives for contractor for finishing ahead of schedule. Six main effects of delay were cost overrun, rescheduling and rearrangement of, litigation, disputes, and arbitration.